REGIONAL GOVERNMENT STRATEGY IN IMPROVING PUBLIC SERVICE PERFORMANCE OF THE PUBLIC RELATIONS SECTION OF THE REGIONAL SECRETARIAT OF GAYO LUES REGENCY - Sabitah Sabitah; Rila Maufira; Nasruddin Nasruddin (SEAN Institute, 2022)
This research aims to find out the strategy and work program of Gayo Lues Regency that has been planned and will be implemented, this can only be done through the Gayo Lues Regency public relations department. This study uses a qualitative descriptive method with observation and literature methods. The results in this study are Gayo Lues Regency Public Relations. has a role in publicizing government activities, namely as a communicator in making and covering government activities, relationships, namely building good relations with internal and external publics, backup management by approaching how the community reacts and responds to posts from the Kampar Regional Secretariat's public relations account, as well as good image markers, namely by creating a positive image for the Government of Gayo Lues Regency. Then it was suggested to Gayo Lues Regency Public Relations, always be active in making news, and asked all Public Relations staff of the Gayo Lues Regency Government to have the ability, visual, to deal with future developments and demands for public services